Isolation of Organism and its Drug Sensitivity Pattern in Patients with Urinary Tract Infection at Kathmandu Model Hospital - Joshi, Rajesh Dhoj; Khadka, Sachin; Joshi, Deepak Man; Shrestha, Basudha; Dangal, Ganesh; Dahal, Abhinav (Nepal Journal of Obstetrics and Gynaecology, 2018)
Introduction: Lack of compliance and unjustified antibiotic prescriptions has resulted in increasing bacterial resistance and is proving as a major challenge in the management of infections. Knowing the commonly isolated uropathogens and their antimicrobial susceptibility is beneficial in planning treatment protocols. Methods: A retrospective review of records of patients with urinary tract infection from January 2012 to December 2016 was conducted at Kathmandu Model Hospital. All patients who were diagnosed as having culture positive urinary tract infection in medical ward of Kathmandu Model Hospital during 5 years period were analyzed for demographic data, prevalence of organism and antibiotic susceptibility patterns. Results: A total of 315 samples were culture positive. The majority of bugs were gram negative E.coli (48.57%) followed by multi-drug resistant E.coli (28.89%). The other major pathogens were E. faecalis (6.03%), S. epidermidis (4.44%), K. pneumoniae (4.13%), respectively. The highest level of sensitivity in first line antibiotics was seen in nitrofurantoin (84.9%), whereas least sensitivity was shown by amoxicillin/clavulanic acid (21%). Similarly, in second line antibiotics, highest sensitivity was seen in tetracycline (100%), imipenem (91.9%) and least to meropenem (49.2%). Ceftazidime is mostly (93.3%) resistant antibiotics among uropathogens. All the third line antibiotics such as polymyxin B, tigecycline and colistin were 100% sensitive to all our isolates. Conclusions: Nitrofurantoin may be an appropriate choice for initial empirical therapy of urinary tract infection. Similarly, the multi-drug resistant E.coli is increasing but it can be tailored if antibiotics are used appropriately on the basis of susceptibility data.